PERAN KONTAK TANI DALAM BUDIDAYA PADI ORGANIK DI KECAMATAN MOJOGEDANG KABUPATEN KARANGANYAR - Rinjani Alam Pratiwi; Suwarto Suwarto; Arip Wijianto (Universitas Sebelas Maret, 2019)
This research aims at studying organic rice cultivation, the role of kontak tani in organic rice cultivation, the relationship between the role of kontak tani and organic rice cultivation, and whether there is a difference among the role of kontak tani according to farmers that is based on farming education, the expanse of farming field and farming environment. The role of kontak tani covers the role as a leader, a model, a preceptor, an activator and an instructor colleague. This research is conducted using quantitative method. The technique of sampling is sensus method with total number of 60 sample respondents from two farming groups under research. The data of the research is analysed using Rank Spearman correlation test dan U Mann Whitney test.The result of the correlation test shows that the relationship between the role of kontak tani as a leader and as a preceptor towards organic rice cultivation is very significant, and the relationship between the role of kontak tani as an activator towards organic rice cultivation is significant, while the role of kontak tani as a model and an instructor colleague towards organic rice cultivation is insignificant. According to U Mann Whitney test, there is no significant differences regarding the role of kontak taniaccording to farmers based on farming education, the expanse of farming field and farming environment.